KAJIAN TINGKAT PELAYANAN JALAN BUNDARAN PU KOTA KUPANG - Dendo, Octavianus E.T.; Sir, Tri M. W.; Hunggurami, Elia (Jurnal Teknik Sipil, 2014)
The high volume traffic that passing through the bundaran PU road caused the meeting of solid vehicles from different direction of street caused the vehicles build up on each direction of road in the morning, afternoon, or evening. The build up of vehicles due to the large number of vehicles that pass on it. therefore the research on these roads has been conducted. In this study, the survey of vehicle volume, the survey of side barriers, and also the survey of the road geometry then analyzed using the calculation Metod of the Indonesian Highway Capacity Manual (MKJI,1997) has been done. Based on the analysis, the maximum volume on Bundaran PU road is 1564.5 SMP/hour with the side barriers 200 m/ hour at busy time on Bundaran PU road is 487.7 SMP/hour. The degree of saturation (DS) on the bundaran PU road based on calculation is 0.80. the level of road service on Bundaran PU road is at D level.